PELATIHAN BACA TULIS AL-QUR’AN INTERAKTIF BAGI JAMAAH MAJELIS TAKLIM DARURROHMAH MUARAGEMBONG - Santia Sari Nurasiah; Siti Asiah; Rabianur Rabianur; Irham Irham (LPPM Universitas Islam 45, 2023)
Majelis Taklim Darurrohmah is one of the taklim assemblies located in Pantai Harapan Jaya Village, Muara Gembong District, Bekasi Regency. The activities in this taklim assembly tend to read surah yasin, tahlil and prayers, therefore the community service programme can improve interactive BTQ learning training for prospective teaching staff of taklim darurrahmah so as to produce ideal and professional teaching candidates. The existing problems are the lack of knowledge of teenagers and housewives about reading and writing the Qur'an and the lack of teaching staff in taklim assemblies. This community service activity uses a TOT (Training Of Trainer) approach which is carried out collaboratively. TOT is research that involves all relevant actions together at this time on a problem to change and improve it. The results of the service related to the training of reading and writing the Koran there are positive changes produced in this Taklim Assembly. The impact is a positive impact in the training of learning to read and write the Qur'an (BTAQ) for the community, especially teenagers and housewives who are increasingly active in learning and following the Darurrohmah Muara Gembong Taklim Assembly.